Ibn Sina on demonstration a logico-epistemological framework of Ibn Sina's philosophy of science - Amran Muhammad (Islamic and Strategic Studies Institute, 2016)
Ibn Sina's conception of demonstration may be divided into two parts. We call the first part the nature of demonstration and the second part the structure of demonstration. In order to understand demonstration, we ought to look into the constitutive elements of scientific knowledge from a micro perspective. For in the nature of demonstration, we actually deal with basic components that make up knowledge, such as conception and assent, definition and description, propositions and syllogisms. From these micro-components of demonstration, we move to the macro-perspective of demonstrative science, attending to it from the structural point of view. The structure of demonstration thus inclues principles, subjects and the problems all of which serves as plillars for demonstrative science.